Tahapan Belajar Orang Bali dalam Gending Rare Ketut Garing - Kadek Dedy Herawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The stages of human learning start from the simplest ways. Gending rare is a way of learning in the early phases of human development. This is because the structure and choice of words in gending rare are easily understood by low cognitive abilities. Through gending rare, an individual can learn basic ways and attitudes of daily life. The study of gending rare Ketut Garing aims to discover fundamental values at every stage of human life. It turns out that these values will not only be useful for the early developmental phases but also for the later stages of development. The method in this study is a qualitative type. This is because the research focuses on the study of oral traditions which are not numerical data. This research resulted in findings that gending rare Ketut Garing played a very important role in shaping children's personality, strengthening adaptive culture, strengthening work culture, teaching a culture of frugality and saving, and giving supremacy to the highest happiness.